Market segmentation strategies and occupancy performance of 4 and 5 star hotels in Klang Valley / Noor Azmi Ahmad - Ahmad, Noor Azmi (2010)
Yield Management (YM) has been described as a method that can help an organization to sell the right inventory, to the right customer, at the right time for the right price (Kimes, 2002). Application of YM strategies involves the company to practice market segmentation strategies; In Malaysia the effect of the application of segmentation strategies on hotel’s revenue management performance is unknown. To illustrate the effect of market segmentation strategy on revenue management performance the measurement used will be revenue per available room (RevPAR) analysis, differs from traditional lodging-market analysis in that it arrives at an estimate of annual room revenue (ARR) by considering average daily rate (ADR) and occupancy levels together rather than treating the two elements separately. This paper seeks to conceptualize the relationship of application of market segmentation strategy and revenue management performance by four (4) and five (5) star hotels in Klang Vallley. Research outcomes will show a positive relationship between hotel that practise market segmentation strategies and revenue management performance. It will also show the segmentation strategies hotel practise to attract most contributing market. For the conclusion, Hotel that practice effective market segmentation will have higher performance compared to other hotel.